(untitled) - Ganzevoort, Reinard Christiaan

A decision support framework for the selection of appropriate time series forecasting methods in the retail sector (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.